ISupport-Brasil: Preliminary results of the usability and acceptability assessment by caregivers of people who have dementia - Ottaviani, Ana Carolina; Monteiro, Diana Quirino; Ferreira Campos, Camila Rafael; Barham, Elizabeth Joan; Oliveira, Déborah; da Cruz, Keila Cristianne Trindade; Corrêa, Larissa; de Souza Orlandi, Fabiana; Zazzetta, Marisa Silvana; Gratão, Aline Cristina Martins; Pavarini, Sofia Cristina Iost (Frontiers in Medicine, 2022)
Objective: To assess usability and acceptability of iSupport-Brasil (iSupport-BR) to virtually support family caregivers of people who have dementia. Method: In the first stage, nine caregivers/former caregivers assessed the interface of the platform that hosts iSupport-BR. In the second stage, 10 caregivers assessed acceptability of the platform and answered the System Usability Scale (SUS), which varies from 0 to 100 points. A descriptive analysis of the quantitative data was performed, as well as a thematic analysis on the open questions. All the ethical aspects were respected. Results: The results of the first stage indicated a user-friendly interface of the system and relevant content of the program, with 55.6% and 77.8% of the participants assigning the maximum grade to these questions, respectively. Of the five possible points, the system's mean score was 3.7. In Stage 2, 80% of the caregivers rated the program as very useful and 100% would recommend it to other caregivers. Perception of the program's usability by the SUS scale was excellent (M = 86.5 ± 11.5). Conclusion: This research allowed elaborating the final version of iSupport-BR, considering usability and acceptability of the platform and the program for computers/notebooks, being a pioneer in evaluating it for use in smartphones. Future research studies will have to assess the effects of iSupport-BR on the caregivers' mental health.